High speed cameras for motion analysis in sports science - Pueo, B. (Journal of Human Sport & Exercise, 2016)
Video analysis can be a qualitative or quantitative process to analyze motion occurring in a single plane using one camera (two-dimensional or 2D) or in more than one plane using two or more cameras simultaneously (three-dimensional or 3D). Quantitative 2D video analysis is performed through a digitizing process that converts body segments or sport implements into digital horizontal and vertical coordinates in the computer. In order for these measurements to be accurate, image capture by means of video cameras must be sharp and motion blur-free, especially in high speed motions. In this paper, a detailed introduction to factors affecting image quality will be presented. Furthermore, selection of the most appropriate camera setting to undertake high speed motion analysis with the best quality possible, both spatially (focus and resolution) and temporally (frame rate, motion blur, shutter options and lighting), will be discussed. Rather than considering commercial criteria, the article will focus on key features to choose the most convenient model both from technical and economical perspectives. Then, a revision of available cameras on the market as of 2015 will be carried out, with selected models grouped into three categories: high-, mid- and low-range, according to their maximum performance in relation to high speed features. Finally, a suggested recording procedure to minimize perspective errors and produce high quality video recordings will be presented. This guideline starts with indications for camera selection prior to purchase or for testing if a given camera would fulfil the minimum features. A good video recording dramatically improves the analysis quality and enables digitizing software to produce accurate measurements.